DIGITAL TOOLS SELECTION FOR INCLUSIVE COURSE DESIGN AT UNIVERSITY - Bilousova, Liudmyla; Gryzun, Liudmyla (The Modern Higher Education Review, 2025)
The paper addresses the currently important issues of building an inclusive learning environment at universities and the design of courses as components of this environment. According to the goals of the work, it explores and elaborates a functional approach to the selection of didactic and digital tools that provide a design of inclusive learning courses based on the universal learning design (UDL) concept associated with neuropsychology. This includes identifying three large scale brain networks, which are responsible for certain aspects of information perception, information processing, and decision-making. Building on these neuropsychological explorations, we identified the didactic approaches and matched them with the necessary digital tools. This allows for achieving such variability within an inclusive course design for each component of the learning process (supported by a proper large-scale brain network) and at all three levels. In addition, the paper highlights the experience and preliminary results of the pilot implementation of an online course as a component of a virtual inclusive campus, which was designed based on the elaborated approach. After the course piloting, the key findings were summed up, including the strengths and weaknesses of the course. After the improvements, the course is going to be disseminated to a larger cohort of trainees with follow-up empirical research on the students’ satisfaction, level of accessibility, and learning motivation, which makes a prospect of the research.